2015
DOI: 10.1200/jco.2014.59.7351
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism Prophylaxis and Treatment in Patients With Cancer: American Society of Clinical Oncology Clinical Practice Guideline Update 2014

Abstract: Purpose To provide current recommendations about the prophylaxis and treatment of venous thromboembolism (VTE) in patients with cancer. Methods PubMed and the Cochrane Library were searched for randomized controlled trials, systematic reviews, meta-analyses, and clinical practice guidelines from November 2012 through July 2014. An update committee reviewed the identified abstracts. Results Of the 53 publications identified and reviewed, none prompted a change in the 2013 recommendations. Recommendations Most h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
310
1
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 915 publications
(320 citation statements)
references
References 2 publications
4
310
1
5
Order By: Relevance
“…The results of this survey are again in line with this recommendation in that many hematologists/oncologists only offer prophylactic anticoagulation to ambulatory patients with pancreatic cancer or multiple myeloma, as recommended by the ASCO or the National Comprehensive Cancer Network (NCCN) [10,11]. Some also provide prophylaxis for ambulatory lung cancer patients, as has been recommended by the International Society on Thrombosis and Haemostasis (ISTH) [8].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The results of this survey are again in line with this recommendation in that many hematologists/oncologists only offer prophylactic anticoagulation to ambulatory patients with pancreatic cancer or multiple myeloma, as recommended by the ASCO or the National Comprehensive Cancer Network (NCCN) [10,11]. Some also provide prophylaxis for ambulatory lung cancer patients, as has been recommended by the International Society on Thrombosis and Haemostasis (ISTH) [8].…”
Section: Discussionsupporting
confidence: 57%
“…There is uncertainty whether really all hospitalized cancer patients should be offered prophylaxis. The recent American Society of Clinical Oncology (ASCO) guideline update reflects this discussion and concedes that there is inadequate support for routine thromboprophylaxis in cancer patients admitted for minor procedures or short chemotherapy infusion [9,10]. The discomfort with uniform thromboprophylaxis is also reflected in our survey.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Despite this, and accepting 80% power, the required sample size would still be challenging to recruit, especially given the relative rarity of the condition and the expected high prevalence of exclusion criteria (e.g., bleeding tendency). The risk of VTE in NS is similar to the risk of VTE in patients with some active cancers [17], in whom routine anticoagulation is not currently recommended [18]. In contrast, it is also similar to the risk of stroke in patients with AF (a CHA 2 DS 2 -VASc score of 2 carries a risk of stroke of 2.2% per year [19]) in whom anticoagulation is recommended [20].…”
Section: Discussionmentioning
confidence: 65%
“…Current guidance recommends using low-molecular-weight heparin over warfarin, and there is no evidence for the efficacy of direct acting oral anticoagulants 6. There are no guidelines for secondary prevention of cancer-related stroke, though one study showed reduced cerebral embolic signals and D-dimer levels with anticoagulant use 7.…”
Section: Discussionmentioning
confidence: 99%